Sickle cell retinopathy: characterization among patients over 40 years of age - Aguiar,Aline Guerreiro (2020)
Abstract Purpose: This article aims to describe the prevalence of retinal alterations on the indirect binocular ophthalmoscopy exam in patients with sickle cell disease (HbSS or HbSC) who are over 40 years of age. Methods: This is a retrospective study in which patients with sickle cell disease (SCD) with an age group of 40 years or older were attended in a service of retina in Salvador, Brasil on the last 10 years. All patients were submitted to the clinical file filling, which includes the sociodemographic profile, clinical profile and ophthalmologic examination. The patients were divided in two groups (SS or SC), according to genotypic profile of hemoglobinopathy (HbSS or HbSC). The classification of retinopathy was performed according to Goldberg in proliferative and non-proliferative retinopathy. A P-value <0.05 was considered statistically significant. Results: A total of 97 patients (194 eyes) were evaluated, being 44 (45%) of the SC group and 53 (55%) of the SS group. Of the 97 patients, 19 (19.5%) did not present retinal changes and 78 (80,5%) present sickle cell retinopathy. Of the 78 patients with retinopathy, 22 (28%) had nonproliferative sickle retinopathy and 56 (72%) had proliferative alterations. The increase in vascular tortuosity was the most observed nonproliferative sign (26.8% of eyes) in both groups. The SC patients presented a greater proportion of findings of areas of retinal non perfusion (30%) than SS patients (p = 0.015). Conclusion: The results suggest the need for regular ophthalmologic follow-up of patients with SCD, especially in the older age group, due to the high prevalence of 80.5% of findings of sickle cell retinopathy on examination in patients over 40 years old.